Mini-Review: From measurement to prediction—a conceptual paradigm shift in assessing overcrowding in pediatric emergency departments since 2021 - Meßner, Johanna T.; Conrad, Melanie L.; Freuer, Dennis; Meisinger, Christine; Fahlbusch, Fabian B.; Weber, Florian (Frontiers in Pediatrics, 2026)
Overcrowding in pediatric emergency departments (PEDs) is an increasing global challenge. While adult emergency medicine has developed several validated measures to assess overcrowding, pediatric-specific methods remain scarce. In recent years, new approaches have emerged, including the first predictive models capable of anticipating crowding before it occurs. This Mini-Review provides a narrative synthesis of recent conceptual and methodological developments in the measurement and prediction of overcrowding in PEDs, building on the literature published since 2021. It conceptually examines unidimensional metrics, multidimensional scores, and emerging predictive models, emphasizing the shift from retrospective assessment to temporally oriented approaches and the need for pediatric-specific validation and multicenter evaluation.